Modelling Transport of Nitrogen Compounds in Geita Wetland along Mtakuja River - Masawe, Ezrael J.; Kimwaga, Richard; Mwanuzi, Fredrick (Tanzania Journal of Engineering and Technology, 2019)
The impacts of excessive nitrogen loading to streams in a watershed occur in the receiving waters such as rivers at the outlet of the watershed. To quantify the impacts of land use and management practices on the nitrogen loading at the watershed outlet, simulation models are needed that can both predict the nitrogen loading at the edge of individual fields and predict the fate of nitrogen as it moves through the river network to the watershed outlet. This paper presents the results of a model analysis for describing the processes governing transformations and transport of nitrogen compounds (NO3-N and NH4-N) through Mtakuja River in the Geita wetland. The model was made in Soil and Water Assessment Tool (SWAT), a watershed model developed to assess the impact of land management practices on water, sediment and agricultural chemical yields with varying soils, land use and management conditions. Two monitoring stations namely MTSP1 and MTSP2 were established along Mtakuja River. A set of SWAT model inputs representative of the water conditions was collected from the established monitoring stations. The model was calibrated and validated for the prediction of flow and nitrogen compounds (NO3-N and NH4-N) transport, against a set of measured mean monthly monitoring data. Sensitive model parameters were adjusted within their feasible ranges during calibration to minimize model prediction errors. At the gauging station MTSP2, the calibration results showed that the model predicted mean monthly flow within 18% of the measured mean monthly flow with the r2 coefficient and Nash-Sutcliffe (NSE) were 0.84 and 0.82, respectively. At the water quality monitoring station MTSP2, the calibration results showed the model predicted nitrogen compounds (NO3-N and NH4-N) loadings within 21% and 23% of their respective measured mean monthly loadings. The mean monthly comparisons of r 2 values for nitrogen compounds ranged from 0.77 to 0.81 while the Nash-Sutcliffe Efficiency (NSE) values were between 0.72 and 0.73. The model results and field measurements demonstrated that about 70% of the annual nitrogen compounds loadings which would otherwise reach Lake Victoria are retained in the wetland. The Mtakuja river model can therefore be used for prediction of nitrogen compounds (NO3-N and NH4-N) transformation processes in the Geita wetland. Keywords: Ammonia-nitrogen, Geita wetland, Mtakuja River, Nitrate-nitrogen, Soil and Water Assessment Tool (SWAT).